Assessment of Density‐Induced Tracer Movement in Groundwater Velocity Measurements with Point Velocity Probes (PVPs). Issue 4 (19th September 2014) - Schillig, P.C.; Devlin, J.F.; McElwee, C.D.; Walter, K.; Gibson, B.
Abstract The concept of equivalent freshwater head was adapted to predict the conditions under which density‐driven flow would adversely impact measured groundwater velocities using point velocity probes (PVPs). Theoretically, vertical flow will result from any density contrast between the PVP tracer and the groundwater. However, laboratory testing of tracers with salinities ranging from 0 to 2000 mg NaCl/L showed that horizontal velocities could be determined with good accuracy with up to 60% of the total flow being vertical due to density effects in a gravel medium. The available data suggest that density effects are less likely to be pronounced in sandy sediments. The relative amount of vertical flow due to tracer density can be estimated from vertical and horizontal velocities measured with PVPs, or from the ratio of vertical to horizontal hydraulic gradients. The equivalent freshwater gradient produced from a given tracer salinity at 10 °C (a typical groundwater temperature at moderate latitudes) can be estimated from 7.80 × 10−7 × (MNaCl), where MNaCl is the mass of NaCl added, in mg, to 1 L of site groundwater in the mixing of the tracer. Equations for other temperatures were also determined.